1997
DOI: 10.1111/j.1365-2044.1997.068-az0055.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective two‐month audit of the lack of provision of a high‐dependency unit and its impact on intensive care

Abstract: All admissions into a six-bedded intensive care unit were audited prospectively over a 2-month period. Data were collected daily and classified according to criteria for intensive care or high-dependency admission. There were 30 planned admissions (72 bed days) following elective major surgery, seven admissions following semi-elective surgery (41 bed days) and 47 emergency admissions (185 bed days). Overall bed occupancy was 89%. Of 366 possible intensive care days, 66 (23%) were occupied by high-dependency pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…It can function as a physically independent unit or as a dedicated section, incorporated within the ICU [13]. It can act as a “step-up” or “step-down” unit between the general ward and the ICU [35] but can also be used to admit patients from the Emergency Department or Recovery ward [5, 6]. From a historical perspective, most IMCUs originated from specific medical specialties or were introduced for a specific function (i.e., obstetric care, cardiac care), while later adding function and scope [7].…”
Section: Introductionmentioning
confidence: 99%
“…It can function as a physically independent unit or as a dedicated section, incorporated within the ICU [13]. It can act as a “step-up” or “step-down” unit between the general ward and the ICU [35] but can also be used to admit patients from the Emergency Department or Recovery ward [5, 6]. From a historical perspective, most IMCUs originated from specific medical specialties or were introduced for a specific function (i.e., obstetric care, cardiac care), while later adding function and scope [7].…”
Section: Introductionmentioning
confidence: 99%
“…The provision of intermediate care facilities has been advocated to reduce mortality after intensive care. In the absence of randomised controlled trials, there is indirect evidence that the availability of high dependency units (HDUs) may improve outcome after ICU discharge [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Although a difference in length of stay was not demonstrated in our study, other studies have concluded that patients nursed postoperatively in HDUs recover well and are more likely to have a shorter postoperative length of stay than patients of similar acuity nursed on postoperative wards. 3,19 In regard to our findings, it is likely that prior to the establishment of the HDU, some critically ill patients might have been nursed in the ICU rather than the ward, leading to lower acuity and shorter length of stay in the ward group. Closely related to this is an important costbenefit of the HDU-the reduction of unnecessary use of intensive care beds by provision of alternative high level care.…”
Section: Discussionmentioning
confidence: 80%